Eg5 and TPX2 in cohesion fatigue - Yeap, Szu Ling (2015)
The fidelity of chromosome segregation is ensured by organized cleavage of cohesin at the metaphase-to-anaphase transition. However, prolonged metaphase arrest by proteasomal inhibitor MG132 resulted in an asynchronous loss of sister chromatid cohesion, termed cohesion fatigue. Using immunofluorescence staining, live cell imaging and chromosome spread, I observed three phenotypes in cells undergoing cohesion fatigue, namely chromosome scattering, defects in chromosome congression and longer spindle lengths. Inhibition of Eg5 after prolonged metaphase arrest partially rescued cohesion fatigue phenotypes. I also showed that Eg5 dynamics were affected after MG132 treatment, by using various microscopy imaging techniques. Co-immunoprecipitation showed that arresting cells for an extended duration abrogated the interaction of Eg5 with the spindle assembly factor TPX2. Lastly, using Western blotting and radioactive ATP kinase assay, I observed an increase in phosphorylation levels of TPX2 and Aurora A kinase after MG132 treatment. This caused Eg5 motor activity to increase, forcing the spindles to elongate. With that, I found a novel regulatory pathway where Eg5 and TPX2 contribute to cohesion fatigue in mammalian cells.